PENGARUH PERPUTARAN AKTIVA TETAP, LIKUIDITAS, PERPUTARAN KAS TERHADAP RENTABILITAS - tinambunan, riama elfriede; Simanjuntak, Barita Ria Evisstella; Utami, Yuti Tasha; Siallagan, Damai Yanti Meisarah; Simorangkir, Enda Noviyanti (2020)
The objective of this research is to determine the effect of Fixed Assets Turnover, current ratio, cash turnover to profitability in basic and chemical industries company which is listed in The Indonesia Stock Exchange. This research is implemented to 75 basic and chemical industries company which is listed in The Indonesia Stock Exchange. The technique used in sampling is purposive sampling technique based on certain considerations, with a sample of 34 basic and chemical companies.Data of this research which has been used in secondary data. The analysis method used is multiple linear regression, F test andT test. The results of the analysis of this study are the turnover of fixed assets, liquidity, cash turnover simultaneously affect the profitability. While the partial analysis shows that only the turnover of fixed assets and cash turnover has an effect on profitability.